Clinopodium kallaricum—an unexpected new member of the tropical African C. simense group from flora of Iran - Bordbar, Firouzeh; Mirtadzadini, Mansour (Phytotaxa, 2019)
In this study, the taxonomic placement of Satureja kallarica from Zagros mountain range of Iran is assessed using sequence data from the nuclear ribosomal ITS and the plastid trnL-F and matK regions. The findings are discussed on a morphological background. In consequence the species is formally transferred to the genus Clinopodium. It falls into the Clinopodium simense group which was so far restricted to tropical Africa.